2014
DOI: 10.1093/trstmh/tru179
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Acanthamoeba T15: the environmental strain in Turkey

Abstract: In Turkey, this was the first time that Acanthamoeba jacobsi (T15) was detected in water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…Result didn't show any positive samples from geothermal hot spring water of Bandar Abbas. Some studies showed that based on the morphological characteristics of amoebae, 42% of warm spring waters of southwest of Iran are positive for Acanthamoeba, and others revealed that genotype T2, T4, T15 could exist in such environments [12,31]. No significant statistical differences were observed between pH variable and frequency of Acanthamoeba using culture and molecular methods (p-value = 0.014) and p-value (p = 0.116) respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Result didn't show any positive samples from geothermal hot spring water of Bandar Abbas. Some studies showed that based on the morphological characteristics of amoebae, 42% of warm spring waters of southwest of Iran are positive for Acanthamoeba, and others revealed that genotype T2, T4, T15 could exist in such environments [12,31]. No significant statistical differences were observed between pH variable and frequency of Acanthamoeba using culture and molecular methods (p-value = 0.014) and p-value (p = 0.116) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Result didn't show any positive samples from geothermal hot spring water of Bandar Abbas. Some studies showed that based on the morphological characteristics of amoebae, 42% of warm spring waters of southwest of Iran are positive for Acanthamoeba, and others revealed that genotype T2, T4, T15 could exist in such environments [ 12 , 31 ].…”
Section: Main Textmentioning
confidence: 99%
“…Result didn't show any positive samples from geothermal hot spring water of Bandar Abbas. Some studies showed that based on the morphological characteristics of amoebae, 42% of warm spring waters of southwest of Iran are positive for Acanthamoeba, and others revealed that genotype T2, T4, T15 could exist in such environments (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba species encompasses at least 15 species of free living amoebae that have been isolated from a wide range of environments ranging from natural habitats like soil, salt water and fresh water, to domestic sources like tap water, air conditioning units and sewage systems 17 . The researchers have been reported that Acanthamoeba (genotype 4) is pathogen and common in environmental sources 18 . We found that only Acanthamoeba (genotype 4) in soil and water samples as supported in previous studies about Acanthamoeba.…”
Section: Discussionmentioning
confidence: 99%